IMPORTANCE OF ISLAMIC STOCK INDICES FOR THE COUNTRY'S FINANCIAL MARKET (Spectrum Journal of Innovation, Reforms and Development, 2023)
This research delves into the paramount significance of Islamic fund indices as instruments for harmonizing investments with Sharia principles. With their provision of a comprehensive array of investment avenues adhering to ethical standards, these indices play a pivotal role in propelling the growth and dynamism of the Islamic capital market. Against the backdrop of an evolving global financial milieu, these indices assume an increasingly pivotal role, transcending their financial function to exert a compelling influence on the ethical comportment of corporations. This study underscores the critical import of these indices in effecting the seamless integration of deeply ingrained beliefs and contemporary investment paradigms, thereby engendering a just, equitable, and prosperous financial ecosystem for both Islamic and non-Islamic stakeholders.